Ni-based CH4-CO2 reforming catalyst as well as preparation method and application thereof

By using Ni-based catalyst and La and Pr bimetals as support in the CH4-CO2 reforming catalyst, the alloy is formed through electrospinning technology, which solves the problem of the catalyst's activity decrease at high temperatures, and achieves efficient CH4 and CO2 conversion and Improved stability.

CN119281343AInactive Publication Date: 2025-01-10INNER MONGOLIA UNIV OF TECH

Patent Information

Application Number
CN202411813341.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The activity of the existing CH4-CO2 reforming catalysts decreases or is inactivated under high temperature reaction conditions, making it difficult to achieve industrialization of the CH4-CO2 reforming reaction.

Method used

Ni-based catalyst and La and Pr bimetals are used as support to support the active metal Ni through electrospinning technology to form La and Pr alloys, improving the activity and stability of the catalyst and avoiding inactivation caused by carbon deposits.

Benefits of technology

The conversion of CH4 and CO2 is improved at a lower reaction temperature, the high temperature stability of the catalyst is maintained, the service life of the catalyst is extended, the generation of carbon deposits is avoided, and the catalytic performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281343A_ABST
    Figure CN119281343A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of CH4-CO2 reforming catalysts, in particular to a Ni-based CH4-CO2 reforming catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: adding absolute ethyl alcohol into a polyvinylpyrrolidone solution to obtain a dispersion liquid; adding a nickel salt, a lanthanum salt and a praseodymium salt into the dispersion liquid for dissolving to obtain an electrostatic spinning solution; performing electrostatic spinning on the electrostatic spinning solution to obtain a fiber film; roasting the fiber film to obtain a catalyst precursor; and calcining the catalyst precursor to obtain the Ni-based CH4-CO2 reforming catalyst. The Ni-based CH4-CO2 reforming catalyst prepared by the preparation method disclosed by the invention has relatively good catalytic activity and stability; the alloy formed by the La-Pr bimetal greatly improves electron transfer in the reforming reaction process, so that the catalytic activity and catalytic stability of the CH4-CO2 reforming catalyst are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of CH4-CO2 reforming catalysts, and in particular to a Ni-based CH4-CO2 reforming catalyst and a preparation method and application thereof. Background Art

[0002] CH4 and CO2 are the main greenhouse gases and two main carbon sources. The reforming reaction of CH4 and CO2 can not only utilize these two greenhouse gases at the same time, but also the ratio of H2 / CO in the product synthesis gas is 1, which can be directly used as the feed gas of Fischer-Tropsch synthesis to synthesize hydrocarbon compounds with longer carbon chains. This reaction shows extremely high industrial value and environmental benefits for the conversion and utilization of greenhouse gases and the production of clean energy.

[0003] At present, the main reason why CH4-CO2 reforming reaction is difficult to achieve industrialization is the deactivation problem of CH4-CO2 reforming catalyst. At present, active metals such as nickel and cobalt are often used in CH4-CO2 reforming reaction, but under high temperature reaction conditions, the activity of CH4-CO2 reforming catalyst decreases or even deactivates due to factors such as sintering and carbon deposition of active metals. Therefore, it is very necessary to design a CH4-CO2 reforming catalyst with high catalytic activity and good stability. Summary of the invention

[0004] In order to solve the problems of low catalytic activity and poor stability of existing catalysts, the present invention provides a Ni-based CH4-CO2 reforming catalyst and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is a method for preparing a Ni-based CH4-CO2 reforming catalyst, comprising the following steps: adding anhydrous ethanol to the polyvinyl pyrrolidone solution to obtain a dispersion; Adding nickel salt, lanthanum salt and praseodymium salt to the dispersion to dissolve and obtain an electrospinning solution; Electrospinning the electrospinning solution to obtain a fiber film; calcining the fiber film to obtain a catalyst precursor; The catalyst precursor is calcined to obtain the Ni-based CH4-CO2 reforming catalyst.

[0006] The second technical solution of the present invention is a Ni-based CH4-CO2 reforming catalyst prepared by the above-mentioned preparation method.

[0007] The third technical solution of the present invention is the application of the Ni-based CH4-CO2 reforming catalyst in the CH4-CO2 reforming reaction.

[0008] The present invention discloses the following technical effects: 1. The present invention uses metal Ni as the active metal of the catalyst, and La and Pr as carriers. The active metal Ni is successfully loaded onto the La and Pr bimetallic carriers through electrostatic spinning technology, and the electrostatic spinning technology makes the components dispersed evenly. The method of the present invention can form an alloy of La and Pr bimetallic, and the formation of La and Pr alloy greatly promotes electron transfer during the reaction process. Compared with the catalyst of single metal La loaded Ni, the catalyst has a higher CH4 and CO2 conversion rate at a lower reaction temperature.

[0009] 2. The catalyst prepared by the method of the present invention not only has high catalytic activity and high-temperature stability, but also can effectively avoid catalyst deactivation caused by carbon deposition during the catalytic process, and has excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 a, b are scanning electron microscope images of the catalyst precursor NiO-La1Pr1 prepared in Example 1 at different magnifications; c is a scanning electron microscope image of the Ni-La1Pr1 catalyst.

[0012] Figure 2 This is the XRD pattern of the Ni-La1Pr1 catalyst prepared in Example 1.

[0013] Figure 3 The CH4 and CO2 conversion rates were tested for the stability of the Ni-La1Pr1 catalyst prepared in Example 1.

[0014] Figure 4 Scanning electron microscope images of the catalyst precursor NiO-La1Pr2 prepared in Example 2 at different magnifications.

[0015] Figure 5 The CH4 and CO2 conversion rates of the Ni-La1Pr2 catalyst prepared in Example 2 at different reaction temperatures; the left figure is the CH4 conversion rate, and the right figure is the CO2 conversion rate.

[0016] Figure 6 Scanning electron microscope images of the catalyst precursor NiO-La2Pr1 prepared in Example 3 at different magnifications.

[0017] Figure 7The CH4 and CO2 conversion rates of the Ni-La2Pr1 catalyst prepared in Example 3 at different reaction temperatures; the left figure is the CH4 conversion rate, and the right figure is the CO2 conversion rate. DETAILED DESCRIPTION

[0018] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0019] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0020] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0021] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0022] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0023] The "room temperature" described in the present invention, unless otherwise specified, refers to 20-30°C.

[0024] The first aspect of the present invention provides a method for preparing a Ni-based CH4-CO2 reforming catalyst, comprising the following steps: adding anhydrous ethanol to the polyvinyl pyrrolidone solution to obtain a dispersion; Adding nickel salt, lanthanum salt and praseodymium salt to the dispersion to dissolve and obtain an electrospinning solution; The electrospinning solution is electrospinned to obtain a fiber film (fiber diameter 200-400 nm); calcining the fiber film to obtain a catalyst precursor; The catalyst precursor is calcined to obtain the Ni-based CH4-CO2 reforming catalyst.

[0025] In a preferred embodiment of the present invention, the solvent of the polyvinyl pyrrolidone (PVP) solution is N,N-dimethylformamide (DMF); the mass concentration of the polyvinyl pyrrolidone solution is 10% to 13%; and the volume ratio of the anhydrous ethanol to the polyvinyl pyrrolidone solution is 1:(8 to 10).

[0026] In the present invention, when the mass concentration of the polyvinyl pyrrolidone solution is lower than 10%, the solution is too dilute to be electrostatically spun, and thus no fiber can be obtained; when the mass concentration is higher than 13%, the solution is too thick to make spinning difficult, and the spun fibers are too dispersed to be collected on the aluminum foil. At the same time, because polyvinyl pyrrolidone as a sacrificial agent will be completely decomposed during calcination, a high mass proportion of polyvinyl pyrrolidone will cause the fiber morphology to collapse, affecting the generation and morphology of nanotubes.

[0027] In a preferred embodiment of the present invention, the mass fraction of metallic nickel in the electrospinning solution is 0.4% to 0.5%.

[0028] In a preferred embodiment of the present invention, the mass fraction of metallic lanthanum in the electrospinning solution is 4% to 5%.

[0029] In a preferred embodiment of the present invention, the molar ratio of the lanthanum salt to the praseodymium salt is 1:2 to 2:1.

[0030] The nickel salt is at least one of nickel nitrate, nickel acetate and nickel acetylacetonate; the lanthanum salt is lanthanum nitrate; and the praseodymium salt is praseodymium nitrate.

[0031] In a preferred embodiment of the present invention, the electrospinning parameters are set as follows: syringe pump flow rate 8-12 μL / min; applied voltage 14-17 kV; spinning distance 18-20 cm.

[0032] In a preferred embodiment of the present invention, the calcination is specifically as follows: firstly heating the temperature to 250-300°C at a heating rate of 2-6°C / min and keeping the temperature for 2-3 h, and then heating the temperature to 650-750°C at a heating rate of 2-6°C / min and keeping the temperature for 3-4 h.

[0033] After the calcination is completed, the step of naturally cooling to room temperature is also included.

[0034] In a preferred embodiment of the present invention, the calcination is specifically as follows: firstly heating the temperature to 700-800°C at a heating rate of 5°C / min in a nitrogen atmosphere, then introducing hydrogen and keeping the temperature for 2-3 h.

[0035] The second aspect of the present invention provides a Ni-based CH4-CO2 reforming catalyst prepared by the above-mentioned preparation method.

[0036] The third aspect of the present invention provides the use of the Ni-based CH4-CO2 reforming catalyst in a CH4-CO2 reforming reaction.

[0037] The present invention uses metal Ni as the active metal of the catalyst and La and Pr as carriers. The active metal and carrier precursor salts (lanthanum salt and praseodymium salt) are mixed into a spinning solution, and the spinning solution is prepared into La-Pr Ni-supported composite nanofibers by electrostatic spinning. The nanofibers are calcined in air and then reduced in a hydrogen atmosphere to obtain a Ni-based CH4-CO2 reforming catalyst. By regulating the content of La and Pr in the carrier component, a composite catalyst with La-Pr supporting Ni in different proportions is obtained. The alloy formed by La-Pr in the catalyst greatly improves the stability between the active metal and the carrier. The carrier alloy formed between the active metal Ni and the bimetal (La, Pr) also greatly promotes the electron transfer between the reaction processes.

[0038] The addition ratio of La and Pr also has a great influence on the catalytic performance of the catalyst, among which the catalyst with La:Pr of 1:1 has the best catalytic activity. The catalyst can make the prepared Ni-based CH4-CO2 reforming catalyst have better affinity for carbon dioxide, so as to make up for the problem that carbon dioxide diffuses slowly in the catalyst pore structure due to its larger molecular weight than methane, so that carbon dioxide can diffuse into the catalyst pore structure faster and react with the intermediate carbon generated by the decomposition of methane in the catalyst in time, thereby avoiding the generation of carbon deposition.

[0039] Characterization proves that the catalyst with La:Pr ratio of 1:1 has the most oxygen vacancies, and the LaPr alloy further improves the interaction between the active metal Ni and the carrier. The catalyst has the highest initial activity in the CH4-CO2 reforming reaction, and the catalytic activity does not decrease after 50 hours of continuous reaction. The excellent catalytic stability of the catalyst is attributed to the high concentration of oxygen vacancies adsorbing and providing oxygen species during the reaction, causing the catalyst to produce trace carbon deposits. Finally, the strong interaction between Ni and the LaPr carrier also prevents the active metal Ni from sintering and agglomerating during the reaction, thereby maintaining good catalytic stability.

[0040] The Ni-based CH4-CO2 reforming catalyst prepared by the present invention has good catalytic activity and stability; the alloy formed by the La-Pr bimetallic greatly improves the electron transfer during the reforming reaction, and the strong interaction between the active metal Ni and the bimetallic carrier improves the anti-sintering performance of the active metal, thereby effectively improving the catalytic activity and catalytic stability of the CH4-CO2 reforming catalyst.

[0041] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0043] Example 1 This embodiment provides a method for preparing a Ni-based CH4-CO2 reforming catalyst (Ni-La1Pr1 catalyst), the steps are as follows: Step (1), preparing 20 g of a PVP / DMF solution with a mass fraction of 12% PVP, adding anhydrous ethanol with a volume fraction of 1 / 10 to the PVP / DMF solution to obtain a dispersion, and then adding nickel nitrate, wherein the mass fraction of active metal Ni in the solution is 0.4%, and after stirring, obtaining a uniform metal dispersion; Add lanthanum nitrate and praseodymium nitrate in a molar ratio of 1:1 to the metal dispersion, wherein the mass fraction of metal La in the dispersion is 4%, and then stir at high speed at room temperature until the metal salt is completely dissolved; Step (2), after stirring the uniform solution, electrospinning was started, the solution was sucked into a syringe, the infusion rate was set to 9 μL / min, the spinning voltage was 16 kV, the spinning distance was 19 cm, and the fiber film was collected through aluminum foil every four hours; Step (3), the obtained fiber membrane is placed in a tubular furnace and calcined in an air atmosphere, firstly, the temperature is raised to 250°C at a heating rate of 5°C / min, and pre-oxidation treatment is performed for 2 hours. After the pre-oxidation is completed, the temperature is raised to 700°C at a heating rate of 5°C / min, and calcination is continued for 3 hours, and then naturally cooled to obtain the catalyst precursor NiO-La1Pr1.

[0044] Step (4), placing the catalyst precursor in the tubular furnace again, filling the tube with nitrogen and then heating it at a heating rate of 5°C / min, and after heating to 800°C, introducing high-purity hydrogen to reduce the catalyst precursor NiO-La1Pr1 for 2 h to obtain a Ni-La1Pr1 catalyst.

[0045] Step (5), press the Ni-La1Pr1 catalyst into tablets in a tablet press, crush it in a mortar, and then collect the catalyst particles using an 80-mesh screen.

[0046] At the same time, Ni-La2O3 (Ni-La) and Ni-Pr2O3 (Ni-Pr) catalysts were also prepared as comparative samples. Compared with Example 1, the preparation method of the comparative sample only omitted the step of adding lanthanum nitrate or praseodymium nitrate, and the remaining steps and parameters were the same as those of Example 1. When lanthanum nitrate was not added, Ni-Pr2O3 (Ni-Pr) catalyst was prepared, and when praseodymium nitrate was not added, Ni-La2O3 (Ni-La) catalyst was prepared.

[0047] Figure 1 Figures a and b are scanning electron microscope images of the catalyst precursor NiO-La1Pr1 that has not been reduced with H2. It can be seen from the figure that the catalyst presents a nano hollow short tube morphology, and the diameter of the nanotube is generally uniform; Figure 1 Figure c is a scanning electron microscope image of the Ni-La1Pr1 catalyst after H2 reduction. It can be seen from the figure that the morphology of the catalyst is well maintained and consistent with that before reduction.

[0048] Figure 2 This is the XRD diagram of the Ni-La1Pr1 catalyst reduced by H2. It can be seen from the figure that the Ni-La1Pr1 catalyst prepared after H2 reduction presents the peak of LaPr alloy.

[0049] The catalyst prepared in this example is used to catalyze the CH4-CO2 reforming reaction. The catalyst morphology is a nano hollow short tube, and a LaPr alloy is formed. The formation of the alloy will produce a large number of oxygen vacancies, which will provide oxygen ions and oxygen adsorption sites for the reaction intermediates. The catalyst is then tested for stability (the results are shown in FIG. Figure 3 The reaction conditions are: the flow rate of methane and carbon dioxide is 10 mL / min, the reaction temperature is 850℃, and the catalytic activity of the catalyst is still good after 50h, only the conversion rate of methane has a slight decrease, but it is still 89%.

[0050] Example 2 This embodiment provides a method for preparing a Ni-based CH4-CO2 reforming catalyst (Ni-La1Pr2 catalyst), the steps are as follows: Step (1), preparing 20 g of a PVP / DMF solution with a mass fraction of 12% PVP, adding anhydrous ethanol with a volume fraction of 1 / 10 to the PVP / DMF solution to obtain a dispersion, and then adding nickel nitrate, wherein the mass fraction of active metal Ni in the solution is 0.4%, and after stirring, obtaining a uniform metal dispersion; Lanthanum nitrate and praseodymium nitrate are added to the metal dispersion at a molar ratio of 1:2, wherein the mass fraction of metal La in the dispersion is 4%, and then stirred at high speed at room temperature until the metal salt is completely dissolved; Step (2), after stirring the uniform solution, electrospinning was started, the solution was sucked into a syringe, the infusion rate was set to 9 μL / min, the spinning voltage was 16 kV, the spinning distance was 19 cm, and the fiber film was collected every four hours; Step (3), the obtained fiber membrane is placed in a tubular furnace and calcined. First, the temperature is raised to 250°C at a heating rate of 5°C / min and pre-oxidized for 2 h. After the pre-oxidation, the temperature is raised to 700°C at a heating rate of 5°C / min and calcined for 3 h to obtain the catalyst precursor NiO-La1Pr2.

[0051] Step (4), placing the catalyst precursor in the tubular furnace again, filling the tube with nitrogen and starting to heat it at a heating rate of 5°C / min, and after the temperature reaches 800°C, introducing high-purity hydrogen to reduce the catalyst precursor NiO-La1Pr2 for 2 h to obtain a Ni-La1Pr2 catalyst.

[0052] Step (5), press the Ni-La1Pr2 catalyst into tablets in a tablet press, crush it with a mortar, and then collect the catalyst particles with an 80-mesh screen. (That is, the only difference from Example 1 is that the molar ratio of lanthanum nitrate to praseodymium nitrate is 1:2, and the other steps and parameters are the same as Example 1) Figure 4 This is a scanning electron microscope image of the catalyst precursor NiO-La1Pr2 that has not been reduced by H2. It can be seen from the image that the catalyst has a nano-hollow tube morphology, and the diameter of the nanotubes is relatively uniform overall, but the diameter of the short tubes is obviously thicker than that of the short tubes in Example 1.

[0053] The catalyst prepared in this example is used to catalyze CH4-CO2 reforming reaction, and the reaction conditions are: the flow rate of methane and carbon dioxide is 10mL / min, the reaction starting temperature is 650°C, and the final temperature is 850°C. It has been measured that the conversion rates of methane and carbon dioxide at 650°C are 37.4% and 49%, respectively, and the conversion rates at 850°C are 93% and 93.5%, respectively. The conversion rates of methane and carbon dioxide are lower than those of Ni-La1Pr1 catalyst at both low and high temperatures.

[0054] Example 3 This embodiment provides a method for preparing a Ni-based CH4-CO2 reforming catalyst (Ni-La2Pr1 catalyst), the steps are as follows: Step (1), preparing 20 g of a PVP / DMF solution with a mass fraction of 12% PVP, adding anhydrous ethanol with a volume fraction of 1 / 10 to the PVP / DMF solution to obtain a dispersion, and then adding nickel nitrate, wherein the mass fraction of active metal Ni in the solution is 0.4%, and after stirring, obtaining a uniform metal dispersion; Lanthanum nitrate and praseodymium nitrate are added to the metal dispersion at a molar ratio of 2:1, wherein the mass fraction of metal La in the dispersion is 4%, and then stirred at high speed at room temperature until the metal salt is completely dissolved; Step (2), after stirring the uniform solution, electrospinning was started, the solution was sucked into a syringe, the infusion rate was set to 9 μL / min, the spinning voltage was 16 kV, the spinning distance was 19 cm, and the fiber film was collected every four hours; Step (3), the obtained fiber membrane is placed in a tubular furnace and calcined. First, the temperature is raised to 250°C at a heating rate of 5°C / min and pre-oxidized for 2 h. After the pre-oxidation, the temperature is raised to 700°C at a heating rate of 5°C / min and calcined for 3 h to obtain the catalyst precursor NiO-La2Pr1.

[0055] Step (4), placing the catalyst precursor in the tubular furnace again, filling the tube with nitrogen and starting to heat it at a heating rate of 5°C / min, and after the temperature reaches 800°C, introducing high-purity hydrogen to reduce the catalyst precursor NiO-La2Pr1 for 2 h to obtain a Ni-La2Pr1 catalyst.

[0056] Step (5), press the Ni-La2Pr1 catalyst into tablets in a tablet press, crush it with a mortar, and then collect the catalyst particles with an 80-mesh screen. (That is, the only difference from Example 1 is that the molar ratio of lanthanum nitrate to praseodymium nitrate is 2:1, and the other steps and parameters are the same as Example 1) Figure 6 This is a scanning electron microscope image of the catalyst precursor NiO-La2Pr1 that has not been reduced with H2. It can be seen from the image that the catalyst has a nano-hollow tube morphology, and the diameter of the nanotubes is relatively uniform overall, but the diameter of the fiber is significantly thicker than that of Example 1 and Example 2, and there is obvious agglomeration on the fiber surface.

[0057] The catalyst prepared in this example is used to catalyze the reforming reaction of methane and carbon dioxide. The reaction conditions are: the flow rate of methane and carbon dioxide is 10 mL / min, the reaction starting temperature is 650°C, and the final temperature is 850°C. It has been determined that although the conversion rates of methane and carbon dioxide at 650°C are 48.3% and 58.3% respectively, the methane conversion rate is slightly higher than that of the Ni-La1Pr1 catalyst, but the conversion rate at the highest temperature of 850°C is generally lower, which are 87.9% and 90.5% respectively (such as Figure 7 as shown).

[0058] At the same time, Ni-La2O3 and Ni-Pr2O3 catalysts were prepared as comparative samples. The preparation method of the comparative samples was the same as that of Example 3, except that praseodymium nitrate was not added to the Ni-La2O3 catalyst and lanthanum nitrate was not added to the Ni-Pr2O3 catalyst (the total molar amount of metals was the same), and the other conditions were not changed.

[0059] The conversion rates of CH4 and CO2 in the catalytic reforming reaction of methane and carbon dioxide at different temperatures prepared by the catalysts in the above examples are respectively shown in Tables 1 and 2.

[0060] Table 1 Conversion rate of CH4 in the reaction gas of each catalyst catalytic test at different reaction temperatures

[0061] Table 2 Conversion rate of CO2 in the reaction gas of each catalyst catalytic test at different reaction temperatures

[0062] It can be seen from Table 1 and Table 2 that single metal La or Pr and different La and Pr ratios as catalyst carriers have a significant effect on catalyst performance. The catalytic performance of Ni-La catalyst is relatively low, and the catalyst performance is significantly improved after the addition of Pr. The CH4-CO2 reforming catalyst prepared when the molar ratio of La and Pr is 1:1 has the best catalytic performance, and the conversion rates of methane and carbon dioxide at 850°C are 95.3% and 95.9%, respectively. In addition, the experimental results also show that the CH4-CO2 reforming catalyst prepared by the present invention has a high conversion rate of CH4 and CO2 in the catalytic reaction process, although the amount of CH4-CO2 reforming catalyst used is small.

[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a Ni-based CH4-CO2 reforming catalyst, characterized in that: The following steps are involved: adding anhydrous ethanol to the polyvinyl pyrrolidone solution to obtain a dispersion; Adding nickel salt, lanthanum salt and praseodymium salt to the dispersion to dissolve and obtain an electrospinning solution; Electrospinning the electrospinning solution to obtain a fiber film; calcining the fiber film to obtain a catalyst precursor; The catalyst precursor is calcined to obtain the Ni-based CH4-CO2 reforming catalyst.

2. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The solvent of the polyvinyl pyrrolidone solution is N,N-dimethylformamide; the mass concentration of the polyvinyl pyrrolidone solution is 10% to 13%; the volume ratio of the anhydrous ethanol to the polyvinyl pyrrolidone solution is 1: (8 to 10).

3. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The mass fraction of metallic nickel in the electrospinning solution is 0.4% to 0.5%.

4. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The mass fraction of metallic lanthanum in the electrospinning solution is 4% to 5%; the molar ratio of the lanthanum salt to the praseodymium salt is 1:2 to 2:

1.

5. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The nickel salt is at least one of nickel nitrate, nickel acetate and nickel acetylacetonate; the lanthanum salt is lanthanum nitrate; and the praseodymium salt is praseodymium nitrate.

6. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The electrospinning parameters are set as follows: syringe pump flow rate 8-12 μL / min; applied voltage 14-17 kV; spinning distance 18-20 cm.

7. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The calcination is specifically as follows: firstly, the temperature is raised to 250-300° C. at a heating rate of 2-6° C. / min and kept at that temperature for 2-3 h, and then the temperature is raised to 650-750° C. at a heating rate of 2-6° C. / min and kept at that temperature for 3-4 h.

8. The method for preparing a Ni-based CH4-CO2 reforming catalyst according to claim 1, characterized in that: The calcination is specifically as follows: firstly, the temperature is raised to 700-800° C. at a heating rate of 5° C. / min in a nitrogen atmosphere, and then hydrogen is introduced and the temperature is kept for 2-3 hours.

9. A Ni-based CH4-CO2 reforming catalyst prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the Ni-based CH4-CO2 reforming catalyst as claimed in claim 9 in a CH4-CO2 reforming reaction.

Citation Information

Patent Citations

  • Efficient methane and carbon dioxide reforming Ni / SiO2 catalyst and electrostatic spinning preparation method

    CN104511279A

  • Methyl alcohol reforming catalyst and preparation and application thereof

    CN108607564A

  • Preparation method of persulfate catalyst with heterostructure

    CN117414833A

  • Intermediate-temperature fuel cell tailored for efficient utilization of methane

    WO2018017698A2

Cited By

  • One-dimensional high-entropy alloy, preparation method and application of one-dimensional high-entropy alloy in CO2 cycloaddition reaction

    CN121447047A